2009
DOI: 10.3109/02699050903452961
|View full text |Cite
|
Sign up to set email alerts
|

A self-assessment questionnaire for mental fatigue and related symptoms after neurological disorders and injuries

Abstract: In spite of the different aetiology of mental fatigue, the items included in the scale were significant for different diseases with co-occurring mental fatigue. The self-reported scale is suggested to be a valuable tool for assessment of mental fatigue in different diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
145
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 49 publications
4
145
0
Order By: Relevance
“…The Mental Fatigue Scale (MFS) was used for assessment of mental fatigue (Johansson and Rönnbäck, 2014b; Johansson, Starmark, Berglund, Rödholm, & Rönnbäck, 2010) and is based on the definition of mental fatigue suggested by Johansson and Rönnbäck (Johansson and Rönnbäck, 2014a). The MFS is a multidimensional questionnaire comprising 15 questions with a cutoff score of 10.5.…”
Section: Methodsmentioning
confidence: 99%
“…The Mental Fatigue Scale (MFS) was used for assessment of mental fatigue (Johansson and Rönnbäck, 2014b; Johansson, Starmark, Berglund, Rödholm, & Rönnbäck, 2010) and is based on the definition of mental fatigue suggested by Johansson and Rönnbäck (Johansson and Rönnbäck, 2014a). The MFS is a multidimensional questionnaire comprising 15 questions with a cutoff score of 10.5.…”
Section: Methodsmentioning
confidence: 99%
“…The data are taken from previously published studies and also from unpublished studies [27,[30][31][32][33]. In these studies we have used the same assessments with rating scales and cognitive tests, and in this study, we have only used the baseline data taken from these studies.…”
Section: Methodsmentioning
confidence: 99%
“…Usually one or several associated symptoms are common: mood swings, irritability and stress intolerance, trouble with memory, sleep problems, sensitivity to, or intolerance of light and loud noise following overexertion. Typical, associated symptoms are included in MFS and we have previously shown that the included items in MFS have a high internal consistency and are closely connected [27].…”
Section: Assessment Of Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Mental fatigue is commonly observed after a traumatic brain injury, stroke, and infections or inflammatory diseases in the central nervous system [10]. Recently, the mental fatigue scale (MFS) has been developed for subjective evaluation of mental fatigue and related symptoms [9][10][11].…”
Section: Introductionmentioning
confidence: 99%